Review of the genus Cruziohyla (Anura: Phyllomedusidae), with description of a new species - Gray, Andrew R. (Zootaxa, 2018)
The presented work summarises new and existing phenotypic and phylogenetic information for the genus Cruziohyla. Data based on morphology and skin peptide profiling supports the identification of a separate new species. Specimens of Cruziohyla calcarifer (Boulenger, 1902) occurring in Ecuador, Colombia, two localities in Panama, and one in the south east Atlantic lowlands of Costa Rica, distinctly differ from those occurring along the Atlantic versant of Central America from Panama northwards through Costa Rica, Nicaragua, to Honduras. A new species—Cruziohyla sylviae sp. n.—(the type locality: Alto Colorado in Costa Rica)—is diagnosed and described using an integrated approach from morphological and molecular data. Phylogenetic analysis of DNA sequences of the 16S rRNA gene confirms the new species having equal minimum 6.2% genetic divergence from both true C. calcarifer and Cruziohyla craspedopus.